Using Watson Criteria for Analyzing Student Errors: Systematic Literature Review (SLR) - Aswin Aswin; Dadang Juandi (Hipotenusa : Journal of Mathematical Society, 2022)
This study aims to analyze the distribution of research related to the use of the Watson criteria in analyzing student errors at all levels of education. The method used is Systematic Literature Review (SLR). The sample consists of 42 results of qualitative research on the use of Watson's criteria in analyzing student errors. Samples were taken from indexed journals published in the 2017-2021 period. The key question of this research is how the description of the distribution of research related to the use of the Watson criteria in analyzing student errors, is reviewed based on the year of publication, level of research, methods used, number of subjects, types of questions, demographics, and types of errors made by students. Through the SLR method, it was found that there was an increase and decrease in the number of studies over the last five years. Based on the criteria for junior high school level studies, the use of descriptive qualitative methods, using story questions, with less than 30 subjects, and the demographics of research on the island of Java are the most dominant. The most dominant student errors are procedural errors and missing conclusions. This becomes very important to be considered in learning mathematics.